The equation P = 2L + 2W is equivalent to 1. L = p - 2W / 2 2. L = P + 2W / 2 3. 2L = P / 2W 4. L = P - W Explain:
Follow Math Help Forum on Facebook and Google+
Originally Posted by aznmartinjai The equation P = 2L + 2W is equivalent to 1. L = p - 2W / 2 2. L = P + 2W / 2 3. 2L = P / 2W 4. L = P - W Explain: P = 2L + 2W P/2 = L + W L = P/2 - W
Originally Posted by ThePerfectHacker P = 2L + 2W P/2 = L + W L = P/2 - W and if the original poster had put in the brackets this would be answer number 1. RonL
View Tag Cloud